2021
DOI: 10.1002/agj2.20890
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of dual‐purpose rye cover crop as influenced by harvesting date

Abstract: Harvesting annual winter cereal rye (Secale cereale L.) (WCR) as an emergency forage could offset cover crop establishment costs, facilitate WCR adoption, and still provide multiple ecosystem benefits. A five site-year trial was conducted in Colorado (CO) and Illinois (IL) to evaluate the effect of harvest date on WCR forage yield, quality, and its economic performance. From March to April, WCR dry matter (DM) yield increased exponentially in CO and linearly in IL. The DM yield at Julian day (DOY) 112-116 in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…For example, the RFV ranked highest for forage kale overall, and temporal differences were evident for the quality parameters in years 1 and 2 separately. Similar to the results reported by Sadeghpour et al (2021), our experiment revealed that the sampling date had a consistent impact on the forage quality parameters. The early sampling provided greater CP, lower ADF, and NDF concentrations, and greater RFV across all cover crop systems relative to late sampling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the RFV ranked highest for forage kale overall, and temporal differences were evident for the quality parameters in years 1 and 2 separately. Similar to the results reported by Sadeghpour et al (2021), our experiment revealed that the sampling date had a consistent impact on the forage quality parameters. The early sampling provided greater CP, lower ADF, and NDF concentrations, and greater RFV across all cover crop systems relative to late sampling.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results reported by Sadeghpour et al . (2021), our experiment revealed that the sampling date had a consistent impact on the forage quality parameters. The early sampling provided greater CP, lower ADF, and NDF concentrations, and greater RFV across all cover crop systems relative to late sampling.…”
Section: Discussionmentioning
confidence: 53%
“…Similar conditions were observed by Meinerz et al (2011), when evaluating small grain genotypes as single crops, among them, cultivars of black oat, rye and dual-purpose wheat, which presented average values of ADF, after three cuts, of 26.7; 27.4 and 28.6%, respectively. Plant maturity influences forage quality, with yield throughout development tending to increase while quality decreases (Zhao et al, 2020), so later cuts increase NDF concentrations and reduce total digestible nutrients (Sadeghpour et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for the relatively low level of rye grain production in the United States is the grower's profit uncertainty (Sadeghpour et al., 2022; Skarżyńska, 2015; Van Sanford et al., 2022). The main factors influencing cereal profitability are yield, cultivar adaptation, crop management and associated costs, grain quality, and grain price.…”
Section: Introductionmentioning
confidence: 99%